Klasifikasi Tingkat Kepuasan Penggunaan Layanan Teknologi Informasi Menggunakan Decision Tree - Devy Fatmawati; Wulan Trisnawati; Yuwan Jumaryadi; Gandung Triyono (STMIK Budi Darma, 2023)
In order to improve the management of IT services, it is necessary to analyze the satisfaction of service users. One of the determinations of quality service performance is determined from the satisfaction with the service felt by its users. The results of the user satisfaction analysis were carried out by analyzing the results of the Pusintek IT service user satisfaction survey. The Pusintek IT service user satisfaction survey will be conducted for all service users in 2022 using 5 (five) service quality indicators, namely tangible, reliability, responsiveness, assurance, and empathy. The survey results that have been obtained will then be analyzed using a Decision Tree. Based on the results of the tests performed, the accuracy of the decision tree was 98.10% and Naïve Bayes was 97.95%, while for the recall decision tree was 99.51% and Naive Bayes was 98.78%. However, for the level of precision naive bayes, it is better than the decision tree, where the precision naive bayes is 99.02% and the decision tree is 98.47%.